2023
DOI: 10.1186/s12889-023-15467-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between body circumference and testosterone levels and risk of metabolic dysfunction-associated fatty liver disease: a mendelian randomization study

Abstract: Backgroud Body circumference and testosterone levels have been reported as associated with metabolic dysfunction-associated fatty liver disease (MAFLD) risk. However, whether body circumference and testosterone levels play a role in the development of MAFLD remains inconclusive. Methods Using a large database of genome-wide association studies, genetic loci that are independent of each other and strongly associated with body circumference and testo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Consequently, some studies support visceral obesity with WC and BF as primary measures of a crucial risk factor for NAFLD[ 44 ]. Based on European GWAS pooled data, a previous study reported partially different findings compared with our findings, indicating that WHR may be a potential risk factor for NAFLD[ 45 ]. Several factors could explain this difference.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Consequently, some studies support visceral obesity with WC and BF as primary measures of a crucial risk factor for NAFLD[ 44 ]. Based on European GWAS pooled data, a previous study reported partially different findings compared with our findings, indicating that WHR may be a potential risk factor for NAFLD[ 45 ]. Several factors could explain this difference.…”
Section: Discussioncontrasting
confidence: 93%
“…Although previous studies have extensively investigated the relationship between AO and NAFLD, there are limited studies on the association between other anthropometric measures[ 45 , 46 ]. This study expands and validates these results by incorporating a wider range of anthropometric measures, offering additional supporting evidence for a causal association in early-stage NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to decreasing estrogen levels in postmenopausal females, the loss of estrogen-based protection may be the reason for the increased NAFLD risk in these females [ 23 ]. Additionally, testosterone levels in men are considered a potential risk factor for FLD [ 24 ]. No difference was observed in children regarding the risk of Wilson’s disease complicated with FLD based on gender; this related to the fact that children are not sexually mature.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, plasma lipids (TC, TG, HDL, LDL) and alcohol intake frequency were used as exposure factors, and single nucleotide polymorphisms (SNPs) loci significantly associated with the above exposure factors were selected as instrumental variables(IVs), and the outcome variable was OA, and the causal association analysis between exposure and outcome was performed using a two-sample MR analysis approach based on a publicly available genome wide association study (GWAS) database of large samples, and Cochran Q test to assess heterogeneity, and finally sensitivity analysis to verify the reliability of the causal association results. MR analysis needs to satisfy the following three core hypotheses: ①there is a strong association between instrumental variable Z and exposure factor X [ 17 ]; ②instrumental variable Z is not associated with any confounding factor U of the exposure-outcome association; and ③the instrumental variable Z does not affect the outcome Y, except possibly by association with the exposure X [ 18 ]. The two-sample MR study model is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%